Effects of Exogenous Dopamine on the Uptake, Transport, and Resorption of Apple Ionome Under Moderate Drought - Liang, Bowen; Gao, Tengteng; Zhao, Qi; Ma, Changqing; Chen, Qi; Wei, Zhiwei; Li, Cuiying; Li, Chao; Ma, Fengwang (Frontiers in Plant Science, 2018)
The frequency and intensity of water deficits is expected to increase because of global warming. Drought stress is often one of the most limiting factors for plant growth. We conducted greenhouse pot experiments to address how dopamine affects the drought-resistance traits of apple trees at the physiological and molecular levels. Our factorial design consisted of dopamine and no-dopamine applications combined with well-watered and moderate-drought conditions. Seedling biomass, photosynthesis rates, chlorophyll concentrations, and stomatal apertures were markedly reduced under stress but dopamine treatment mitigated the inhibiting effects of drought on plant growth and helped maintain strong photosynthesis, chlorophyll levels, and stomatal functioning. Concentrations of most macro-, micro-, and trace elements decreased in response to drought. This stress also diminished the uptake and transport of elements in the leaves and stems, but increased the partitioning of elements in the roots. Nutrient resorption proficiency (NuRP) decreased while nutrient resorption efficiency (NuRE) increased for most analyzed elements. Exogenous dopamine significantly increased the concentrations, uptake, and transport of nutrients under drought stress, and also altered their distribution within the whole plant. However, this molecule had a negative effect on nutrient resorption. Although transcript levels of a key chlorophyll degradation gene, pheide a oxygenase (PAO), and senescence-associate gene 12 (SAG 12) were elevated upon drought treatment, dopamine significantly suppressed the upregulation of those genes under such stress conditions. These observations indicate that dopamine has an important anti-senescence effect that might be helpful for regulating nutrient uptake, transport, and resorption, and ultimately influencing overall plant growth. Thus, understanding the role of dopamine in drought tolerance introduces new possibilities to use this compound for agricultural purposes.